1998
DOI: 10.1111/j.1572-0241.1998.270_r.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Manifestations of Chagas' Disease

Abstract: Chagas' disease is an infectious disease that affects millions of people in Latin America and is increasingly seen outside endemic areas. A substantial number of patients develop gastrointestinal disorders secondary to lesions of the enteric nervous system. The purpose of this article is to review the current knowledge about gastrointestinal manifestations of Chagas' disease, including disorders other than the well-known gross dilations of esophagus and colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
25

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 32 publications
2
121
0
25
Order By: Relevance
“…Colonic dilatation located in the rectum and sigmoid is better observed by contrast radiography studies and can be detected in up to 80% of cases. However, dilatation can occur only in the rectum, only in the sigmoid, or in the entire colon (277) . It should be emphasized that the clinical picture of severe constipation in patients with idiopathic megacolon who are not infected with T. cruzi is indistinguishable from that induced by Chagas disease (278) .…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Colonic dilatation located in the rectum and sigmoid is better observed by contrast radiography studies and can be detected in up to 80% of cases. However, dilatation can occur only in the rectum, only in the sigmoid, or in the entire colon (277) . It should be emphasized that the clinical picture of severe constipation in patients with idiopathic megacolon who are not infected with T. cruzi is indistinguishable from that induced by Chagas disease (278) .…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Before the discovery of H. pylori, the chronic gastritis commonly seen in chagasic patients, most often in those with the digestive form, had been formerly attributed to biliary duodenal-gastric reflux as well as to hypomotility and hypochlorhydria, resulting in injury to the enteric nervous system caused by T. cruzi infection [9][10][11][12] . Later, some studies demonstrated a high prevalence of H. pylori infection in patients with Chagas disease [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, H. pylori infection is recognized as the main cause of chronic gastritis and is directly linked to the development of peptic ulcer disease as well as gastric carcinoma and MALT lymphoma 4 . Interactions between bacterial virulence, host-related and environmental factors influence the clinical outcome in infected individuals, whereas concurrent infection with other pathogens may also potentially exacerbate or reduce disease severity due to the modulation of the gastric inflammatory process 5-8 .Before the discovery of H. pylori, the chronic gastritis commonly seen in chagasic patients, most often in those with the digestive form, had been formerly attributed to biliary duodenal-gastric reflux as well as to hypomotility and hypochlorhydria, resulting in injury to the enteric nervous system caused by T. cruzi infection [9][10][11][12] . Later, some studies demonstrated a high prevalence of H. pylori infection in patients with Chagas disease [13][14][15][16] .…”
mentioning
confidence: 99%
“…Nevertheless, constipation in association with colonic dilatation shown by radiological studies has been reported previously by other authors. 15 In contrast to barium enema, the anorectal manometry test yielded a much higher prevalence of abnormalities in symptomatic Chagas disease patients with constipation than in the asymptomatic ones, suggesting that such motility disturbances are pathogenetically relevant in the constipation associated with Chagas disease. Previous studies in Chagas disease patients have evidenced colonic hypomotility defined by low basal motility index and low wave frequency in the rectosigmoid, and impairment of the anorectal inhibitory reflex.…”
Section: Discussionmentioning
confidence: 97%